Upaya Indonesia dalam Meningkatkan Kualitas Pariwisata Budaya Melalui Diplomasi Kebudayaan - Adhiningasih Prabhawati (Journal of Tourism and Creativity, 2019)
Abstract Indonesia is a multicultural country that has various ethnicities, races, beliefs, religions, arts and regional cultures. The richness and diversity of Indonesia are one of the main and leadingfactors in national development in Indonesia. National development is carried out by optimizing the potential of culture through the tourism industry, especially cultural tourism. Cultural potential contributes the most to Indonesia because it can generate foreign exchange for the country so that the country’s economy can increase and can create jobs. To realize this, the cooperation between government, stakeholders in the tourism sector, tourism industry actors and society are important to promote tourism, especially the cultural tourism. Similarly, inter-ministerial collaboration needs to be carried out so that the development of Indonesia cultural tourism can be realized and sustainable. Cultural tourism can also be used as a means of diplomacy by Indonesia to promote Indonesia tourism by cooperating with other countries as well as non-government elements both at regional and international level. Therefore, Indonesia’s effort in improving the quality of cultural tourism is through cultural diplomacy. Keywords: tourism, cultural tourism, cultural diplomacy, culture